ANALISIS PENYEBAB ANAK PUTUS SEKOLAH JENJANG SMP DI KELURAHAN TENILO KECAMATAN KOTA BARAT KOTA GORONTALO - Ilahude, Nur Aula M.; Ngiu, Zulaecha; Yunus, Rasid (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to analyze the condition of school dropouts in Tenilo Sub-district, West City District, Gorontalo City; to identify the contributing factors; and to formulate efforts to address the issue. School dropout remains a serious problem in Indonesia’s education system, particularly in areas with low socio-economic conditions. This research employs a qualitative approach with data collection techniques including in-depth interviews, direct observation, and document studies involving dropout students, their parents, teachers, and school officials. The results reveal that the causes of school dropouts are not singular but rather the outcome of complex interactions among various social, economic, cultural, and psychological factors that directly or indirectly influence a child's decision to discontinue their education. Key contributing factors include family financial difficulties, lack of learning motivation, peer influence, social pressure, and inadequate parental supervision. Cultural factors and negative societal perceptions regarding the importance of education also exacerbate the problem. Recommended efforts to address this issue include increasing public awareness about the value of education, providing social assistance, strengthening the role of schools and teachers, and fostering collaboration among government, communities, and educational institutions to create a supportive environment that encourages children's continued participation in education. ABSTRAKPenelitian ini bertujuan untuk menganalisis kondisi anak putus sekolah di Kelurahan Tenilo, Kecamatan Kota Barat, Kota Gorontalo; mengidentifikasi faktor-faktor penyebab anak putus sekolah; serta merumuskan upaya yang dapat dilakukan untuk menanggulangi permasalahan tersebut. Fenomena anak putus sekolah masih menjadi permasalahan serius dalam dunia pendidikan di Indonesia, terutama di daerah dengan tingkat sosial ekonomi yang rendah. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara mendalam, observasi langsung, dan studi dokumentasi terhadap siswa yang putus sekolah, orang tua, guru, serta pihak sekolah. Hasil penelitian menunjukkan bahwa penyebab utama anak putus sekolah tidak bersifat tunggal, melainkan merupakan hasil dari interaksi kompleks berbagai faktor seperti kondisi ekonomi keluarga, kurangnya motivasi belajar, pergaulan bebas, tekanan lingkungan sosial, serta minimnya perhatian dan pengawasan dari orang tua. Selain itu, faktor budaya dan persepsi masyarakat terhadap pentingnya pendidikan turut memperburuk kondisi ini. Upaya penanggulangan yang dapat dilakukan meliputi peningkatan sosialisasi pentingnya pendidikan, pemberian bantuan sosial, penguatan peran sekolah dan guru, serta kolaborasi antara pemerintah, masyarakat, dan lembaga pendidikan dalam menciptakan lingkungan yang mendukung keberlanjutan pendidikan anak.